2019
DOI: 10.3390/f10080609
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Climate and Nutrient Cycles on Forest Response to Global Change: The Role of Mixed Forests

Abstract: Forest ecosystems are undergoing unprecedented changes in environmental conditions due to global change impacts. Modification of global biogeochemical cycles of carbon and nitrogen, and the subsequent climate change are affecting forest functions at different scales, from physiology and growth of individual trees to cycling of nutrients. This review summarizes the present knowledge regarding the impact of global change on forest functioning not only with respect to climate change, which is the focus of most st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 258 publications
(413 reference statements)
1
19
0
Order By: Relevance
“…Conversely, biodiversity has a positive effect on forest productivity (Duffy, Godwin, & Cardinale, ), as mixed‐species forest communities have been demonstrated to be more productive (Huang et al, ; Liang et al, ) and more consistent in productivity over time than monocultures (del Río et al, ; Jucker, Bouriaud, Avacaritei, & Coomes, ; Morin, Fahse, de Mazancourt, Scherer‐Lorenzen, & Bugmann, ; Schnabel et al, ), resulting in higher amounts of carbon stored above‐ and below‐ground in species‐rich forests (Liu et al, ). Yet, despite advances in our understanding of biodiversity–productivity relationships (BPRs), the role of biodiversity in mitigating adverse effects of climate change on the functioning of forest ecosystems remains controversial (Ammer, ; González de Andrés, ; Grossiord, ; Hisano, Chen, Searle, & Reich, ; Hisano, Searle, & Chen, ), making predictions of ecosystem responses to climate change challenging. For example, it has been shown that the strength of BPRs at the community scale was higher in forest types or at forest sites associated with adverse climatic conditions (Jucker et al, ; Paquette & Messier, ), but the opposite response was revealed for forest sites along a global precipitation gradient (Jactel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, biodiversity has a positive effect on forest productivity (Duffy, Godwin, & Cardinale, ), as mixed‐species forest communities have been demonstrated to be more productive (Huang et al, ; Liang et al, ) and more consistent in productivity over time than monocultures (del Río et al, ; Jucker, Bouriaud, Avacaritei, & Coomes, ; Morin, Fahse, de Mazancourt, Scherer‐Lorenzen, & Bugmann, ; Schnabel et al, ), resulting in higher amounts of carbon stored above‐ and below‐ground in species‐rich forests (Liu et al, ). Yet, despite advances in our understanding of biodiversity–productivity relationships (BPRs), the role of biodiversity in mitigating adverse effects of climate change on the functioning of forest ecosystems remains controversial (Ammer, ; González de Andrés, ; Grossiord, ; Hisano, Chen, Searle, & Reich, ; Hisano, Searle, & Chen, ), making predictions of ecosystem responses to climate change challenging. For example, it has been shown that the strength of BPRs at the community scale was higher in forest types or at forest sites associated with adverse climatic conditions (Jucker et al, ; Paquette & Messier, ), but the opposite response was revealed for forest sites along a global precipitation gradient (Jactel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to determine whether the mortality of trees in drought-affected areas will be concentrated in specific competitive and climatic conditions because this determination will enable forest managers to effectively identify areas that are more vulnerable to drought. Large-scale, consistent monitoring of forest ecosystems plays a key role in preparing for the impact of extreme events on the stability of forests [18].…”
Section: Forest Threats Related To Global Warmingmentioning
confidence: 99%
“…In addition, modifying litterfall composition and production rate with thinning or changes in canopy type [20,56] could also modify CWD mesofauna communities, as they are also directly connected to litter communities and vice versa [57]. Under the current paradigm of moving from pure to mixed Scots pine-European beech forests in Europe [15,16], our results should be taken into account both from the biodiversity perspective and from the carbon and nutrient cycling perspective [2], as invertebrate communities influence CWD decay rates [9,[57][58][59]. Consequently, we recommend considering the ecological role of CWD mesofauna when planning silvicultural practices, particularly in mixed forests.…”
Section: Interactions Among Variables and Management Implicationsmentioning
confidence: 99%